ANALISIS DETERMINAN DATA STATISTIK SEKTORAL GEOSPASIAL DAN KEUANGAN TERHADAP PERENCANAAN PEMBANGUNAN MELALUI APLIKASI TANGERANG SATU DATA SEBAGAI VARIABEL INTERVENING - Mukhlishotin, Iffi Nur; Darmojo, Hardjito S.; Ismail Muzakir , M. Athar (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This research is motivated by the less than optimal utilization of sectoral statistical data, geospatial data, and financial data in the Tangerang Satu Data Application for the preparation of development planning carried out by Regional Apparatus Organizations (OPD). This research was conducted in OPD within the Tangerang City Government. This research uses a quantitative method with an electronic questionnaire instrument that is distributed digitally to ASN who have the authority to prepare planning in each OPD as respondents. This study uses path analysis using two models. Based on the results of the first model study, it was found that sectoral statistical data (X1), geospatial data (X2), and financial data (X3) have a significant direct effect on the Tangerang one data application (Z). And in the second structural model, it was found that sectoral statistical data (X1), geospatial data (X2), financial data (X3), and Tangerang One data application (Z) have a significant direct effect on development planning (Y). However, when the sectoral statistical data variables (X1), geospatial data (X2), and financial data (X3) through the Tangerang one data application (Z) have no significant influence on development planning (Y). While simultaneously, sectoral statistical data, geospatial data, financial data, and the Tangerang One Data application have a significant direct influence on OPD development planning within the Tangerang City Government with a correlation coefficient value of 88%. This study recommends the Tangerang City Government conduct massive socialization of the use of the Tangerang Satu Data Application so that OPDs get more accurate data for development planning within the Tangerang City Government that is more targeted, effective, and efficient. Keywords: Sectoral Statistical Data, Geospatial Data, Financial Data, Tangerang Satu Data Application, Development Planning